Endovascular Therapy of Anterior Circulation Tandem Occlusions: Pooled Analysis From the TITAN and ETIS Registries. Issue 10 (October 2021) - Anadani, Mohammad; Marnat, Gaultier; Consoli, Arturo; Papanagiotou, Panagiotis; Nogueira, Raul G.; Siddiqui, Adnan; Ribo, Marc; Spiotta, Alejandro M.; Bourcier, Romain; Kyheng, Maeva; Labreuche, Julien; de Havenon, Adam; et al.
Abstract : Background and Purpose: Endovascular therapy for tandem occlusion strokes of the anterior circulation is an effective and safe treatment. The best treatment approach for the cervical internal carotid artery (ICA) lesion is still unknown. In this study, we aimed to compare the functional and safety outcomes between different treatment approaches for the cervical ICA lesion during endovascular therapy for acute ischemic strokes due to tandem occlusion in current clinical practice. Methods: Individual patients' data were pooled from the French prospective multicenter observational ETIS (Endovascular Treatment in Ischemic Stroke) and the international TITAN (Thrombectomy in Tandem Lesions) registries. TITAN enrolled patients from January 2012 to September 2016, and ETIS from January 2013 to July 2019. Patients with acute ischemic stroke due to anterior circulation tandem occlusion who were treated with endovascular therapy were included. Patients were divided based on the cervical ICA lesion treatment into stent and no-stent groups. Outcomes were compared between the two treatment groups using propensity score methods. Results: A total of 603 patients were included, of whom 341 were treated with acute cervical ICA stenting. In unadjusted analysis, the stent group had higher rate of favorable outcome (90-day modified Rankin Scale score, 0–2; 57% versus 45%) and excellent outcome (90-day modified Rankin Scale score, 0–1; 40% versus 27%) compared with the no-stent group. In inverse probability of treatment weighting propensity score–adjusted analyses, stent group had higher odds of favorable outcome (adjusted odds ratio, 1.09 [95% CI, 1.01–1.19]; P =0.036) and successful reperfusion (modified Thrombolysis in Cerebral Ischemia score, 2b-3; adjusted odds ratio, 1.19 [95% CI, 1.11–1.27]; P <0.001). However, stent group had higher odds of any intracerebral hemorrhage (adjusted odds ratio, 1.10 [95%, 1.02–1.19]; P =0.017) but not higher rate of symptomatic intracerebral hemorrhage or parenchymal hemorrhage type 2. Subgroup analysis demonstrated heterogeneity according to the lesion type (atherosclerosis versus dissection; P for heterogeneity, 0.01), and the benefit from acute carotid stenting was only observed for patients with atherosclerosis. Conclusions: Patients treated with acute cervical ICA stenting for tandem occlusion strokes had higher odds of 90-day favorable outcome, despite higher odds of intracerebral hemorrhage; however, most of the intracerebral hemorrhages were asymptomatic. Abstract : Supplemental Digital Content is available in the text.